2021
DOI: 10.1371/journal.pone.0256211
|View full text |Cite
|
Sign up to set email alerts
|

Emotional arousal in 2D versus 3D virtual reality environments

Abstract: Previous studies have suggested that virtual reality (VR) can elicit emotions in different visual modes using 2D or 3D headsets. However, the effects on emotional arousal by using these two visual modes have not been comprehensively investigated, and the underlying neural mechanisms are not yet clear. This paper presents a cognitive psychological experiment that was conducted to analyze how these two visual modes impact emotional arousal. Forty volunteers were recruited and were randomly assigned to two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 36 publications
5
24
1
Order By: Relevance
“…This phenomenon may be considered from the inverse U-shaped model of arousal levels [ 48 ]. VR has been shown to increase emotional arousal recorded by multichannel electroencephalograms [ 49 , 50 ], which is consistent with our results showing that the VR-EX condition had a greater arousal increase than the 2D-EX condition. Although exercise-induced increases in intraparticipant arousal levels measured by the TDMS have been associated with enhanced cognitive function and prefrontal activity, which controls cognitive processing [ 25 ], excessively increased arousal levels related to high intensity exercise [ 51 ] or stress [ 52 ] may counteract the beneficial effects of exercise on cognitive function.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon may be considered from the inverse U-shaped model of arousal levels [ 48 ]. VR has been shown to increase emotional arousal recorded by multichannel electroencephalograms [ 49 , 50 ], which is consistent with our results showing that the VR-EX condition had a greater arousal increase than the 2D-EX condition. Although exercise-induced increases in intraparticipant arousal levels measured by the TDMS have been associated with enhanced cognitive function and prefrontal activity, which controls cognitive processing [ 25 ], excessively increased arousal levels related to high intensity exercise [ 51 ] or stress [ 52 ] may counteract the beneficial effects of exercise on cognitive function.…”
Section: Discussionsupporting
confidence: 92%
“…Neuroimaging research has shown that human brains are more attuned to complex, naturalistic stimuli over those that are simple and artificial [15]. VR technology can be customized to present three-dimensional images [16][17][18], create the illusion of distant sounds [19,20], and provide haptic feedback to create engaging, multimodal stimuli that represent the lived experiences of research participants [21][22][23]. VR can also incorporate a high degree of control in a realistic and multisensory environment, ideal for high quality basic research.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic channels selected for statistical analysis of EEG were frontal region (Fz, F3, F4, FCz, FC3, FC4), parietal region (Pz, P3, P4), central region (Cz, C3, C4, CP3, CP4), temporal region (TP7, TP8, T7, T8, P7, P8), and occipital region (POz, PO3, PO4, Oz, PO7, PO8) [31]. The subjects' EEG data were acquired via Neuroacle EEG Recorder V2.0.1, a toolbox of the software Matlab 2016 (Math Works, USA), with a sampling frequency of 1000 Hz and electrode impedances all less than 5 kQ.…”
Section: Data Recording and Processingmentioning
confidence: 99%
“…where k represents the number of trials in the data segment (k = 1 in this experiment), n represents the number of data points in each segment, and x(k) i represents the value of the ith point in the kth data segment [31].…”
Section: Data Recording and Processingmentioning
confidence: 99%